The influence of alendronate on bone formation after autogenous free bone grafting in rats - (:unkn) unknown (MOSBY-ELSEVIER, 2005)
Objective. This study was undertaken to investigate the influence of alendronate on bone formation after autogenous free bone grafting in rats. Study design. Fifty-six male Wistar-Albino rats were divided into 3 groups: baseline, saline-treated, and alendronate-treated groups, and followed up at 2, 4, and 12 weeks. In the femur of the rats, autogenous free bone grafts 3 mm in diameter and 2 mm in length were harvested with a standard trephine bur. The bone defects 3 mm in diameter and 2 mm in length were created 5 mm from the donor sites. Each graft was placed in the bone defect and stabilized by perifemoral wiring. The a I end roil ate-treated rats were administered 0.25 mg/kg alendronate subcutaneously daily. The saline-treated rats were given daily saline solution. Serum calcium, phosphate, parathyroid hormone, 1,25-dihydroxyvitamin D, bone alkaline phosphatase (BAP), osteocalcin, and urine calcium were measured. The changes in the number of osteoblasts bordering active bone formation surface and osteoid and lamellar bone formation were evaluated to measure anabolic bone activity. Results. Alendronate caused significant increase in serum osteocalcin and BAP levels biochemically and the number of osteoblasts histopathologically. Conclusion. Alendronate may be considered among therapeutic options to improve bone formation process in different bone remodeling cases. Further detailed studies should be focused on closage- and time-dependent effects of alendronate on bone formation.
Keywords: MUCOPERIOSTEAL FLAP SURGERY; BISPHOSPHONATE ALENDRONATE; EXPERIMENTAL PERIODONTITIS; POSTMENOPAUSAL WOMEN; CYCLICAL ETIDRONATE; RESORPTIVE PHASE; ROOT RESORPTION; PAGETS-DISEASE; LOCAL-DELIVERY; IN-VITRO